Detection of vancomycin-resistant enterococci (VRE) in stool specimens submitted for Clostridium difficile toxin testing - İLKİ, ZEYNEP ARZU (SOC BRASILEIRA MICROBIOLOGIA, 2017)
The aim of this study was to determine the association between Clostridium difficile (C. difficile) and vancomycin-resistant Enterococcus (VRE) and efficacy of screening stools submitted for C. difficile toxin assay for prevalence of VRE. Between April 2012 and February 2014, 158 stool samples submitted for C. difficile toxin to the Marmara University Microbiology Laboratory, were included in the study. Stool samples were analyzed by enzyme immuno assay test; VIDAS (bioMerieux, France) for Toxin A&B. Samples were inoculated on chromID VRE (bioMerieux, France) and incubated 24 h at 37 degrees C. Manuel tests and API20 STREP (bioMerieux, France) test were used to identify the Enterococci species. After the species identification, vancomycin and teicoplanin MIC's were performed by E test and molecular resistance genes for vanA vs vanB were detected by polymerase chain reaction (PCR). Of the 158 stool samples, 88 were toxin positive. The prevalence of VRE was 17%(n:19) in toxin positives however, 11.4% in toxin negatives(n:70). All VRE isolates were identified as Enterococcus faecium. These results were evaluated according to Fischer's exact chi-square test and p value between VRE colonization and C. difficile toxin positivity was detected 0.047 (p < 0.05). PPV and NPV were 79% and 47% respectively. In our study, the presence of VRE in C. difficile toxin positives is statistically significant compared with toxin negatives (p < 0.05). Screening for VRE is both additional cost and work load for the laboratories. Therefore VRE screening among C. difficile toxin positive samples, will be cost effective for determination of high risk patients in the hospitals especially for developing countries (C) 2017 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Clostridium difficile; Enterococci; Vancomycin resistance (VRE); Colonizationa; RISK-FACTORS; COLONIZATION; FAECIUM; EPIDEMIOLOGY; INFECTION; CARRIAGE; FAECALIS; SPREAD; ASSAY; AGAR